2005
DOI: 10.1152/ajpheart.00019.2005
|View full text |Cite
|
Sign up to set email alerts
|

Increasing donor age adversely impacts beneficial effects of bone marrow but not smooth muscle myocardial cell therapy

Abstract: We evaluated the impact of donor age on the efficacy of myocardial cellular therapy for ischemic cardiomyopathy. Characteristics of smooth muscle cells (SMC), bone marrow stromal cells (MSCs), and skeletal muscle cells (SKMCs) from young, adult, and old rats were compared in vitro. Three weeks after coronary ligation, 3.5 million SMCs (n = 11) or MSCs (n = 9) from old syngenic rats or culture medium (n = 6) were injected into the ischemic region. Five weeks after implantation, cardiac function was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 23 publications
4
80
1
Order By: Relevance
“…A negative correlation between donor age, number and proliferative capacity of MSCs isolated from young and old donors has been demonstrated by several authors (Martin et al 1970, Schneider & Mitsui 1976, Majors et al 1997, D'Ippolito et al 1999, Stenderup et al 2003, Mareschi et al 2006, but widely different results have been obtained with regard to MSC antigen expression. Recently, Stolzing et al (2008) confirmed those already demonstrated in previous studies (D 'Ippolito et al 1999, Mendes et al 2002, Chen et al 2005, Zhang et al 2005, Zheng et al 2007, Kretlow et al 2008, observing a significant age-related change in membrane markers expression levels, an alkaline phosphatase activity, chondrogenic and myogenic differentiation potency decline with donor age in contrast with adipogenic differentiation. However, these data are in contrast with those reported by other research groups (Bergman et al 1996, Stenderup et al 2001, Bellows et al 2003, which showed no age-related differences in differentiation potency.…”
Section: Introductionsupporting
confidence: 85%
“…A negative correlation between donor age, number and proliferative capacity of MSCs isolated from young and old donors has been demonstrated by several authors (Martin et al 1970, Schneider & Mitsui 1976, Majors et al 1997, D'Ippolito et al 1999, Stenderup et al 2003, Mareschi et al 2006, but widely different results have been obtained with regard to MSC antigen expression. Recently, Stolzing et al (2008) confirmed those already demonstrated in previous studies (D 'Ippolito et al 1999, Mendes et al 2002, Chen et al 2005, Zhang et al 2005, Zheng et al 2007, Kretlow et al 2008, observing a significant age-related change in membrane markers expression levels, an alkaline phosphatase activity, chondrogenic and myogenic differentiation potency decline with donor age in contrast with adipogenic differentiation. However, these data are in contrast with those reported by other research groups (Bergman et al 1996, Stenderup et al 2001, Bellows et al 2003, which showed no age-related differences in differentiation potency.…”
Section: Introductionsupporting
confidence: 85%
“…31 Moreover, transplantation of BMC from aged rats did not improve heart function after MI. 32 Subgroup analysis based on the study by Cao also suggested that younger patients might benefit more from BMC infusion than older patients. 19 In the second instance,more significant LVEF improvementwas observed when BMC were administered 6 or 7 days after acute MI compared to 5 days after acute MI.…”
Section: Discussionmentioning
confidence: 99%
“…Perinatal sources seem attractive, with greater frequency and higher proliferative-potential MSCs, but a major limitation is that MSCs can typically only be isolated from around one-third of umbilical cord blood specimens [1,2]. Earlier fetal, placental, and amniotic sources yield abundant primitive MSCs with greater differentiative ability than later sources [5,6], but they require invasive procedures and/or access to abortal tissue, with its attendant ethical issues. There is thus a major unmet need for new sources of MSCs for clinical application.…”
Section: Introductionmentioning
confidence: 99%